Pro-Environmental Behavior of Indonesian Household Consumers Toward Single-Use Packaging (Application of the Extended Theory of Planned Behavior) - Melly Indrawaty; Popy Novita Pasaribu; Lucky Hikmat Maulana (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The increasing use of single-use plastic packaging has created serious environmental problems, while housewives, as the primary decision-makers in household consumption, play a crucial role in promoting sustainable behavior. This study aims to analyze the factors influencing sustainable consumption behavior among housewives in Bogor City by applying the Extended Theory of Planned Behavior (ETPB). Using a Likert-scale questionnaire, the research involved 219 housewife respondents in Bogor City. Data were analyzed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that green purchase intention serves as a mediator influencing sustainable consumption behavior, while environmental knowledge and religious-cultural factors exert a direct effect on sustainable consumption behavior. These results highlight the importance of strengthening attitudes, socialization processes, and environmental knowledge through education, campaigns, and the role of religious and cultural figures, along with the provision of environmentally friendly products to foster sustainable consumption.